Elevated Progestin-Related Immunoreactivity is Positively Associated with Bleeding Severity in Women with Intramural Uterine Fibroids - Abd Alkareem, Tamara Ahmed; Jamai, Mataz J.; Sami, Mohammed Mahdi (The Prodia Education and Research Institute (PERI), 2026)
BACKGROUND: Uterine fibroids is an intentional cause of recurrent uterus bleeding. As a synthetic progestin, medroxyprogesterone acetate (MPA) is sequentially used as a medication for extensive uterine bleeding and have been broadly studied in gynecological field research. However, its role as a serum hormonal marker in fibroid-related bleeding remains poorly elucidated. Therefore, current study was conducted to evaluate serum progestin-related immunoreactivity (PRI) as biochemical parameter to examine its relation with the severity of bleeding in patients suffering from intramural uterine fibroids obtained among different menopausal statuses.METHODS: A cross-sectional study including 90 individuals with intramural uterine fibroids was conducted. Subjects were classified into a reproductive-age and post-menopausal. Blood samples were collected for biochemical parameter analysis, and clinical as well as anthropometric assessments were performed. MPA, serum levels of luteinizing hormone (LH), follicle-stimulating hormone (FSH), and Vitamin D3 were determined using enzyme-linked immunosorbent assay (ELISA). While fasting blood glucose (FBG) levels were determined using the glucose oxidase–peroxidase.RESULTS: Circulating PRI, represented by MPA concentration, was markedly elevated in reproductive-age with mean of 4.57±1.45 compared with the postmenopausal group (1.30±0.59). In reproductive-age subjects, PRI levels showed a significant p<0.001 positive and strong association in comparison to bleeding duration, fibroid mass size, bleeding severity and body mass index (BMI) with r-values of 0.72, 0.53, 0.57, 0.67 respectively. A significant p<0.001 associations in postmenopausal group were seen between PRI and bleeding duration, bleeding severity, and BMI with r-values of 0.66, 0.53, 0.70 in that order. By contrast, the correlation between FBG and PRI was weak in both study groups, indicating a limited association between FBG and PRI.CONCLUSION: This study demonstrates that higher levels of PRI markedly linked with increasing severity of bleeding and longer bleeding duration in patient with intramural uterine fibroids across both study group, indicating that PRI levels reflects progestin-related immunoreactive signals associated with fibroid-related bleeding severity therefore might be potential as biochemical parameter.KEYWORDS: medroxyprogesterone acetate, intramural fibroids, uterine bleeding, reproductive age, postmenopause